Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Kelas V UPTD SDN Sumolawang Pada Mata Pelajaran Matematika Materi Bangun Ruang - Lia Khabibatul Maula (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aims to determine the significant improvement of students' mathematics learning outcomes through the application of the Problem Based Learning (PBL) learning model. This research is a quantitative research with a type of experimental research, the design used is quasi experimental design with nonequivalent control group design. Sampling using non-probability sampling techniques with the type of Saturated Sampling. The sample used amounted to 52 students from class V UPTD SDN Sumolawang, This study only used control classes and experimental classes. Data were collected using structured interviews and question tests, the instrument trials used were validity tests and reliability tests, while data analysis used normality tests, homogeneity tests. Test the hypothesis using the Mann Whitney Test, based on the results of the calculation analysis of Sig. (2-Tailed) 0.328 > 0.05 then Ho is accepted and Ha is rejected. This means that there is no difference in learning outcomes from the control group and experimental group, it can be concluded that there is no influence of the Problem Based Learning (PBL) learning model on the learning outcomes of grade V students of UPTD SDN Sumolawang in mathematics subjects building space material.